Screening of Probiotics Derived from Chopped Chili and Its Application in Fermented Chopped Chili - Qian YANG; Luyao XIAO; Xuhong BAI; Yufang TIAN; Wei LI (Shipin gongye ke-ji)
In order to develop probiotics fermented chopped chili with good flavor and certain nutrition and health effects, the traditional fermented chopped chili was collected from Hunan and utilized as raw material to screen probiotic strains that could be tolerant to gastrointestinal digestion in this study. The influence of probiotics fermentation on the physicochemical properties, safety, and sensory properties of chopped chili was investigated using physicochemical analysis, sensory evaluation, and non-targeted metabolomics techniques. Results indicated that three strains tolerant to gastrointestinal digestion were obtained, identified as Lactiplantibacillus plantarum JEB2, Lactobacillus brevis JEB7, and Saccharomyces cerevisiae JEE2, respectively. Among them, L. plantarum JEB2 and L. brevis JEB7 completely degraded 0.25 mg/mL of sodium nitrite within 24 h and S. cerevisiae JEE2 exhibited a cholesterol assimilation rate of 50.79% within 24 h. Chopped chili fermented with all the three strains exhibited a pH<4.2, titratable acidity>0.6%, and obviously lower nitrite content and coliform count compared to naturally fermented chopped chili. Notably, the sensory score of chopped chili fermented with a combination of L. plantarum JEB2 and L. brevis JEB7 reached the highest value of 19.50 (full marks of 20). Furthermore, the non-targeted metabolomics results revealed a downregulation in the expression levels of irritant substances (4-acetamido-2-amino butanoic acid and sparteine) in this chopped chili sample, whereas the expression levels of aromatic substances (4-methyl benzaldehyde, ethyl brassylate, D-sorbitol, etc.) and bioactive compounds (phytol, diosgenin, kaempferol, etc.) were upregulated. Therefore, the chopped chili fermented with a combination of L. plantarum JEB2 and L. brevis JEB7 was beneficial to reduce the irritancy, improve the product flavor, safety and health-promoting properties, which was expected to be further developed as fermentation starters for the production of fermented products.